Kolaborasi Guru dan Orang Tua Dalam Membentuk Kesadaran Lingkungan Melalui Pembelajaran Ekosistem - Mulyani, Indah Destia; Wuryastuti, Sri; Suratno, Tatang (Universitas Pendidikan Indonesia Kampus Serang, 2021)
Cleanliness of the environment is very important in life on this earth, we as living things, especially humans who have reason and mind, must be able to take good care of the surrounding environment. Because the living things that live on this earth influence each other. if we can take good care of nature or the environment, it will create a good, clean environment that makes humans or animals comfortable, and vice versa if we destroy nature or the surrounding environment, we will feel the bad effects. This research aims to form environmental awareness in order to protect the surrounding environment properly. Learning that can be practiced directly one of them is science subjects, as well as material that can be taught to students through ecosystem materials. Because in this ecosystem material it is explained that every living thing needs and influences one another. This study uses the narrative inquiry method which in the delivery is in the form of a narrative or story to make it easier for the reader to understand it. The results of the research obtained by the researcher were increasing environmental awareness in students, the application of environmental care activities, and students knowing the forms of interaction between living things with one another. Researchers who act as teachers, in the process of learning many things from students to form environmental awareness, are very interesting things to research. Also, the most important thing is that a teacher and parent must be able to collaborate well in the child's learning process.